Pemakaian Sistem Venturi Scrubber– EGR (Exhaust Gas Recirculation) Terhadap Performa Mesin Diesel Satu Silinder - Samuel Parlindungan Siregar; Joni Joni; Obet Takke Ranteallo (G-Tech: Jurnal Teknologi Terapan, 2024)
Reusing exhaust gas based on potential energy that has not been completely burned can absorb heat in the combustion chamber thereby increasing the performance of diesel engines. The aim of this research is to determine the effect of using an EGR venturi scrubber on the performance of a single cylinder diesel engine. This research was carried out on a single cylinder diesel motorbike with a capacity of 200cc. Testing was carried out using an EGR venturi scrubber with valve variations of 10%, 20% and 30% compared to standard (0% EGR). Test data was obtained through VDAS technology software by loading the water entering the dynamometer at the test installation. The research results showed that testing using the EGR venturi scrubber on diesel motorbikes had an influence on engine performance. The best performance was obtained by using a venturi scrubber with a valve opening of 30%, where at a maximum rotation of 3000 rpm the torque was 6.57 Nm, the effective power was 2110 Watts, the average effective pressure was 4.72 bar, the specific fuel consumption was 0 .0549 kg/kWh, and a thermal efficiency of 58.42%.